Addition of long-acting beta2-agonists to inhaled steroids as first line therapy for persistent asthma in steroid-naive adults and children - Ni Chroinin, Muireann (2009)
BACKGROUND: Consensus statements recommend the addition of long-acting inhaled ß2-agonists (LABA) only in asthmatic patients who are inadequately controlled on inhaled corticosteroids (ICS). It is not uncommon for some patients to be commenced on ICS and LABA together as initial therapy. OBJECTIVES: To compare the efficacy of combining inhaled corticosteroids with long-acting ß2-agonists (ICS+LABA) with inhaled corticosteroids alone (ICS alone) in steroid-naive children and adults with persistent asthma. We assessed two protocols: (1) LABA + ICS versus a similar dose of ICS (comparison 1) and (2) LABA + ICS versus a higher dose of ICS (comparison 2). SEARCH METHODS: We identified randomised controlled trials through electronic database searches (May 2008). SELECTION CRITERIA: Randomised trials comparing ICS + LABA with ICS alone in children and adults with asthma who had no inhaled corticosteroids in the preceding 28 days prior to enrolment. DATA COLLECTION AND ANALYSIS: Each author assessed studies independently for risk of bias and extracted data. We obtained confirmation from the trialists when possible. The primary endpoint was rate of patients with one or more asthma exacerbations requiring rescue systemic corticosteroids. Results are expressed as relative risks (RR) for dichotomous data and as mean differences (MD) or standardised mean differences (SMD) for continuous data. MAIN RESULTS: Twenty-eight study comparisons drawn from 27 trials (22 adult; five paediatric) met the review entry criteria (8050 participants). Baseline data from the studies indicated that trial populations had moderate or mild airway obstruction (FEV1 65% predicted), and that they were symptomatic prior to randomisation. In comparison 1, the combination of ICS and LABA was not associated with a significantly lower risk of patients with exacerbations requiring oral corticosteroids (RR 1.04; 95% confidence interval (CI) 0.73 to 1.47) or requiring hospital admissions (RR 0.38; 95% CI 0.09 to 1.65) compared to a similar dose of ICS alone. The combination of LABA and ICS led to a significantly greater improvement from baseline in FEV1 (0.12 L/sec; 95% CI 0.07 to 0.17), in symptoms (SMD −0.26; 95% CI −0.37 to −0.14) and in rescue ß2-agonist use (−0.41 puffs/day; 95% CI −0.73 to −0.09) compared with a similar dose of ICS alone. There was no significant group difference in the risk of serious adverse events (RR 1.15; 95% CI 0.64 to 2.09), any adverse events (RR 1.02; 95% CI 0.96 to 1.09), study withdrawals (RR 0.95; 95% CI 0.82 to 1.11), or withdrawals due to poor asthma control (RR 0.94; 95% CI 0.63 to 1.41). In comparison 2, the combination of LABA and ICS was associated with a higher risk of patients requiring oral corticosteroids (RR 1.24; 95% CI 1 to 1.53) and study withdrawal (RR 1.31; 95% CI 1.07 to 1.59) than a higher dose of ICS alone. For every 100 patients treated over 43 weeks, nine patients using a higher dose ICS compared to 11 (95% CI 9 to 14) on LABA and ICS suffered one or more exacerbations requiring rescue oral corticosteroids. There was a high level of statistical heterogeneity for FEV1 and morning peak flow. There was no statistically significant group difference in the risk of serious adverse events. Due to insufficient data we could not aggregate results for hospital admission, symptoms and other outcomes. AUTHORS’ CONCLUSIONS: In steroid-naive patients with mild to moderate airway obstruction, the combination of ICS and LABA does not significantly reduce the risk of patients with exacerbations requiring rescue oral corticosteroids over that achieved with a similar dose of ICS alone. However, it significantly improves lung function, reduces symptoms and marginally decreases rescue ß2-agonist use. Initiation of a higher dose of ICS is more effective at reducing the risk of exacerbations requiring rescue systemic corticosteroids, and of withdrawals, than combination therapy. Although children appeared to respond similarly to adults, no firm conclusions can be drawn regarding combination therapy in steroid-naive children, given the small number of children contributing data.